Pelatihan Pembuatan Ecoprint dengan Teknik Pounding dan Sosialisasi Kewirausahaan Desa Kauman dalam Upaya Pemanfaatan Potensi Alam untuk Meningkatkan Perekonomian - Prastica, Diva Ariestya; Novella, Cindy; Rahmawati, Monica (Jurnal Bina Desa, 2023)
Kauman Village is in Comal District, Pemalang Regency. This village has various natural potentials that can be utilized to improve the economy of the surrounding residents. In an effort to exploit this natural potential, Unnes Community Service Giat 5 held a Training Activity for Making Ecoprints with Pounding Techniques and Entrepreneurship Socialization, which aims to provide new knowledge and techniques regarding the manufacture of fabrics using natural dyes which do not have a negative effect on environmental health and provide information on marketing digital as a modern and renewable means of selling. The method used is entrepreneurship socialization, training and demonstrations of making ecoprints with pounding techniques. This training produced new skills for PKK Kauman Village cadres in making cloth with natural dyes and provided a new understanding of marketing techniques that are widely used.Keywords: (ecoprint, pounding,digital maketing,)